THE EFFECTIVENESS OF DICTATION TECHNIQUE IN TEACHING WRITING ABILITY - Samsul Hakim (JURNAL ASIMILASI PENDIDIKAN, 2024)
This study aimed at examining the effectiveness of Dictation Technique in teaching writing. There were two statements of problems formulated (1) is Dictation Technique effective in teaching writing skill for the eighth grade students of MTs. Ziadatussyakirin NW Sikur in the school year 2022-2023? (2) How is the effectiveness of Dictation Technique in teaching writing for the eighth grade students of MTs. Ziadatussyakirin NW Sikur in the school year 2022-2023? The result of this is the mean score of pre-test was 9.75 and the mean score of the post-test was 19.45. It meant that, there was a significant difference in the mean score between the pre-test and post-test. In testing hypothesis, the present researcher found that t (df= 24) = 14.99, at p = 0.000. it showed that the value of significant level (p value) was much lower than 0.05. It meant that alternative hypothesis was accepted. This implied Dictation activity was effective in teaching writing for the eighth grade students of MTs. Ziadatussyakirin NW Sikur in the school year 2022-2023.